2022
DOI: 10.31234/osf.io/yrngz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brazilian math teacher’s magnitude representation and strategy use in fraction comparison: a mixed methods study

Abstract: Fractions have a fundamental importance in the design and construction of mathematical knowledge, being the basis for algebra and other advanced mathematical content (BAILEY et al., 2012; BOOTH; NEWTON, 2012; SIEGLER et al., 2012; TORBEYNS et al., 2015). However, historically this representational form of rational numbers has presented several obstacles in the teaching and learning process, both for students and teachers (PINTO, 2011; SERRAZINA; RODRIGUES, 2018; SIEGLER; THOMPSON; SCHNEIDER, 2011). One of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Although there was virtually no difference between their accuracy on compatible (94.9%) and misleading (91.1%) trials with common components, high-achieving students were worse at comparing compatible (69.7%) than misleading (89.7%) trials. This pattern of stronger performance on misleading than compatible has been reported in mathematicians (Obersteiner et al, 2013) and math teachers (Toledo et al, 2023). Such a pattern of performance may reflect the use of the gap strategy.…”
Section: High School Students' Fraction Comparison Strategy Profilessupporting
confidence: 70%
See 3 more Smart Citations
“…Although there was virtually no difference between their accuracy on compatible (94.9%) and misleading (91.1%) trials with common components, high-achieving students were worse at comparing compatible (69.7%) than misleading (89.7%) trials. This pattern of stronger performance on misleading than compatible has been reported in mathematicians (Obersteiner et al, 2013) and math teachers (Toledo et al, 2023). Such a pattern of performance may reflect the use of the gap strategy.…”
Section: High School Students' Fraction Comparison Strategy Profilessupporting
confidence: 70%
“…Consistent with these predictions, math teachers (Toledo et al, 2023) and even mathematicians (Obersteiner et al, 2013) show both componential and rational distance effects, but componential distances modulate performance as predicted by their relation with rational distance. Critically, when the effects of rational and componential distances are contrasted, rational distance has the strongest modulation (Toledo et al, 2023), suggesting that, at least among highly proficient individuals, the effects of componential distance may be partially explained by the intertwined relation between these distances and rational distance. In the Common Component block, the relations between rational and componential distance (for the metrics that varied) were strong and positive.…”
Section: Studymentioning
confidence: 62%
See 2 more Smart Citations
“…Several studies have demonstrated that rational numbers display distance effects Bonato et al, 2007;DeWolf et al, 2014;Hurst & Cordes, 2016;Hurst & Cordes, 2018;Kalra, Binzak, Matthews, & Hubbard, 2020). More recent efforts have attempted to disentangling the effects of rational vs. whole distance (Ischebeck et al, 2009;Obersteiner, Van Dooren, Van Hoof, & Verschaffel, 2013;Toledo, Abreu-Mendoza, & Rosenberg-Lee, 2022, August 10). These studies have focused on fractions, where the actual rational distance between fraction pairs has been contrasted with the distance between the components (numerators and denominators).…”
Section: Discussionmentioning
confidence: 99%